Nitrofurantoin-Associated Acute Granulomatous Interstitial Nephritis. (March 2021) - Anupama, B. K.; Sampat, Parth; Gambhir, Harvir S.
We report the case of a 71-year-old female who was incidentally found to have nonoliguric acute kidney injury on a routine workup for new-onset visual hallucination. Further history revealed inadvertent usage of nitrofurantoin for 3 months for an anticipated urological procedure. Renal biopsy demonstrated acute granulomatous interstitial nephritis. The renal function significantly improved following discontinuation of nitrofurantoin and corticosteroid administration. We highlight a rare association of nitrofurantoin with acute granulomatous interstitial nephritis through this case report.